Accessibility for Line-Cutting in Freeform Surfaces. (September 2019) - Sosin, Boris van; Bartoň, Michael; Elber, Gershon
Abstract: Manufacturing techniques such as hot-wire cutting, wire-EDM, wire-saw cutting, and flank CNC machining all belong to a class of processes called line-cutting where the cutting tool moves tangentially along the reference geometry. From a geometric point of view, line-cutting brings a unique set of challenges in guaranteeing that the process is collision-free. In this work, given a set of cut-paths on a freeform geometry as the input, we propose a conservative algorithm for finding collision-free tangential cutting directions. These directions, if they exist, are guaranteed to be globally accessible for fabricating the geometry by line-cutting. We then demonstrate how this information can be used to generate globally collision-free cut-paths. We apply our algorithm to freeform models of varying complexity. Highlights: An algorithm for finding possible cutting tangent lines in freeform surfaces. Cutting tangent lines are guaranteed to be gouging-free, up to a bounded error. Resulting cutting lines are used for generating obstruction-free cutting paths. Applicable for hot-wire cutting, wire-saw cutting, wire EDM, and similar processes.